2020
DOI: 10.3168/jds.2019-17991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum zinc-methionine supplementation on feed digestibility, rumen fermentation patterns, immunity status, and passive transfer of immunity in dairy cows

Abstract: The aim of this study was to determine the effects of prepartum supplementation of zinc-methionine (Zn-Met) on feed digestibility, rumen fermentation patterns, and immunity status in dams and passive immunity transfer in their calves. A randomized complete design was used in this study. Forty multiparous Holstein dairy cows in late pregnancy (60 d before the expected calving date) were blocked by parity (2.1 ± 0.3), body weight (651 ± 52 kg), and expected calving date, and randomly assigned to 1 of 4 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…ZM supplementation reportedly enhanced the resistance to infection by increasing the total immunoglobulin concentration in weaning calves (29). In addition, a recent study demonstrated that ZM supplementation increased the concentrations of IgA and IgM in the colostrum of dairy cows (33). In the present study, we found that not only ZM, but also ZP increased the plasma IgG concentrations.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…ZM supplementation reportedly enhanced the resistance to infection by increasing the total immunoglobulin concentration in weaning calves (29). In addition, a recent study demonstrated that ZM supplementation increased the concentrations of IgA and IgM in the colostrum of dairy cows (33). In the present study, we found that not only ZM, but also ZP increased the plasma IgG concentrations.…”
Section: Discussionsupporting
confidence: 72%
“…Researches have shown that zinc suppresses pro-inflammatory cytokines production, whereas zinc deficiency induces the production of pro-inflammatory cytokines such as IL-1β and IL-6 (35). Chen et al (33) suggested that the blood concentration of IL-1 in dairy cows decreased linearly, with the dose of ZM increasing. So far, there are few studies on the effect of ZP on plasma cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…tion period, whereas in our study we performed total replacement of STM by OTM sources in both pre-and postpartum TMRs. Chen et al (2020) reported that supplementation of Zn-methionine given to prepartum cows increased DMI linearly, with increasing inclusion levels from 0 to 60 mg/kg of DM. Changes in feed intake are normally accompanied by changes in feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing a diet with Zn vs. no supplemental Zn has previously been shown to increase dietary N digestibility or retention in some studies ( Carmichael et al, 2018 , 2019 ; Alijani et al, 2020 ). However, the majority of studies showed no effect of Zn sources on N digestibility and retention ( Pino and Heinrichs, 2016 ; Faulkner and Weiss, 2017 ; Alijani et al, 2020 ; Chen et al, 2020 ). Nevertheless, Daniel et al (2020) observed that dietary CP digestibility decreased by a 1% unit when an organic form of Cu, Mn, and Zn (proteinate) replaced 30% of the inorganic form of these minerals.…”
Section: Discussionmentioning
confidence: 99%